Application of ROS 2-Based Linorobot2 Framework on A Boxy Mobile Robot - Iman Hakimi Shah; Zakaria, Mohamad Fauzi (Evolution in Electrical and Electronic Engineering, 2026)
This project implements the linorobot2 framework, integrated with Robot Operating System 2 (ROS 2), on a custom-built Boxy mobile robot. The main goal is to create a reliable system for manually controlling this differential-drive robot indoors. A Raspberry Pi 4 running ROS 2 Humble serves as the main computer, managing high-level ROS 2 nodes for communication and control. Simultaneously, a Raspberry Pi Pico microcontroller handles low-level motor control and processes data from wheel encoders, communicating with the ROS 2 system using micro-ROS. The robot utilises a YD LiDAR sensor for environmental data acquisition, supporting future mapping and localisation. While the current focus is on manual control via keyboard teleoperation, the project lays the foundation for fully autonomous navigation using the Navigation2 (Nav2) framework. The results demonstrate that the Linorobot2 framework provides a modular and scalable platform for low-cost mobile robotics in education and research.